[tex]4 + \frac{1}{7} = 4 \frac{1}{7} [/tex]
[tex]2 \frac{5}{9} + 7 \frac{1}{9} = 9 \frac{6}{9} = 9 \frac{1}{3} [/tex]
[tex]2 \frac{7}{8} + \frac{1}{8} = 3[/tex]
[tex]3 + \frac{4}{9} = 3 \frac{4}{9} [/tex]
[tex] \frac{8}{10} - \frac{7}{10} = \frac{1}{10} [/tex]
[tex]4 \frac{9}{5} - 1 \frac{1}{5} = 3 \frac{8}{5} = 4 \frac{3}{5} [/tex]
[tex]1 - \frac{1}{6} = \frac{5}{6} [/tex]
[tex]8 - 3\frac{1}{4} = 4 \frac{3}{4} [/tex]
[tex] \frac{2}{3} - 5 = - 4 \frac{1}{3} [/tex]
[tex]6 \times 2 \frac{1}{3} = \frac{6}{1} \times \frac{7}{3} = \frac{42}{3} = 14[/tex]